2019
DOI: 10.3389/fphar.2019.01083
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Biotransformation of Gliclazide and the Effect of Deoxycholic Acid in a Probiotic Bacteria Model

Abstract: Introduction: Inter-individual differences in gut microflora composition may affect drug metabolism and overall therapeutic response. Gliclazide is a drug characterized by large inter-individual differences in therapeutic response; however, the causes of these differences are not fully explained and may be the outcome of microbial biotransformation. Recently, great attention has been paid to studies on bile acid (BA) interactions with gut microflora and the role of BAs in the modification of drug transport thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…Beyond the increasingly recognized scenario of biotransformation by the bacterial enzymes, in a previously published study, we have demonstrated that drugs may also accumulate in gut bacteria ( Đanić et al, 2019 ). To the best of our knowledge, no previous research had considered drug-bacteria interactions in terms of bioaccumulation so this type of interaction is a completely new aspect that needs special attention in future studies to gain a more in-depth understanding of its influence on drug bioavailability.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Beyond the increasingly recognized scenario of biotransformation by the bacterial enzymes, in a previously published study, we have demonstrated that drugs may also accumulate in gut bacteria ( Đanić et al, 2019 ). To the best of our knowledge, no previous research had considered drug-bacteria interactions in terms of bioaccumulation so this type of interaction is a completely new aspect that needs special attention in future studies to gain a more in-depth understanding of its influence on drug bioavailability.…”
Section: Introductionmentioning
confidence: 86%
“…The tubes were incubated at anaerobic conditions at 37°C for 24 h, gently shaking the tubes occasionally. Extracellular and intracellular medium samples were collected and prepared for the LC-MS analysis at predetermined time points (0 min, 15 min, 1 h, 2 h, 4 h, 6 h, 24 h) according to previously published procedure ( Đanić et al, 2019 ). In each time point, after the gentle shaking the tubes to uniformly distribute the content, 100 μL of samples were withdrawn and centrifuged for 5 min at 15,000 rpm to precipitate bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…В настоящее время выявляются все новые факторы, влияющие на вариабельность гликемии. Так, появились данные о вовлечении в процесс гликолиза и гидролиза гликлазида кишечной микрофлоры, индивидуальность взаимодействия которой с пробиотиками, например, дезоксихолевой кислотой, определяет индивидуальность действия ПСМ и нивелирование высокой вариабельности гликемии [18]. Установлено также, что представители класса ПСМ, за исключением гликлазида, оказывают влияние на рецепторы, активируемые пероксисомными пролифераторами γ PRRAγ, способствуя набору массы тела [19].…”
Section: контрольная группа «глибенкламид» Punclassified
“…The secondary bile acid, DCA, is known for its ability to increase membrane permeability in various physiological settings [ 159 , 160 , 161 , 162 ]. A study by Lalić-Popović et al [ 159 ] investigated the effects of DCA on the permeability of gliclazide across the blood–brain barrier in healthy and diabetic rats.…”
Section: Bile Acidsmentioning
confidence: 99%